2016
DOI: 10.14710/ijfst.11.2.94-98
|View full text |Cite
|
Sign up to set email alerts
|

KOMPOSISI PENYUSUN TERUMBU KARANG TEPI (FRINGING REEF) DI PULAU MANDANGIN KABUPATEN SAMPANG, MADURA The Composition of Fringing Reef Formation in Pulau Mandangin, Sampang Province, Madura

Abstract: ABSTRAKTerumbu karang tepi di Pulau Mandangin tersusun substrat biotik dan abiotik dengan kedalaman tidak lebih dari 40 m. Pulau Mandangin adalah pulau kecil yang memiliki komposisi substrat dasar seperti terumbu karang dan perairannya yaitu zona leeward dan zona windward. Zona leeward adalah sisi yang membelakangi arah datangnya angin, sedangkan zona windward adalah sisi yang menghadap arah datangnya angin. Tujuan dari penelitian ini adalah untuk mengetahui komposisi penyusun terumbu karang tepi (fringing ree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
1
1
1
Order By: Relevance
“…The number of coral lifeforms found in the Tengah patchreef was considered high by the occurrence of all coral lifeform categories. This finding was different compared to the works ofGuntur et al (2016) and Rosi et al (2016) conducted in Mandangin Island of Sampang Regency which only found 2-5 lifeforms. Similar studies done by Ginoga et al (2016) reported six lifeforms in East Ratatotok Village of South Minahasa Regency.…”
contrasting
confidence: 81%
“…The number of coral lifeforms found in the Tengah patchreef was considered high by the occurrence of all coral lifeform categories. This finding was different compared to the works ofGuntur et al (2016) and Rosi et al (2016) conducted in Mandangin Island of Sampang Regency which only found 2-5 lifeforms. Similar studies done by Ginoga et al (2016) reported six lifeforms in East Ratatotok Village of South Minahasa Regency.…”
contrasting
confidence: 81%
“…Ekosistem penting yang ada di perairan laut adalah salah satunya ekosistem terumbu karang, hal tersebut dapat ditinjau dari segi ekologi maupun biotanya. Terumbu karang memiliki fungsi sebagai wadah makanan yang produktif untuk perikanan, tempat hidup beranekaragam hewan laut dan juga sebagai tempat memijah, secara fisik terumbu karang memiliki fungsi sebagai pemecah ombak dan pelindung pantai dari serangan badai (Guntur et al, 2016). Manfaat terumbu karang yang besar juga memiliki potensi ancaman yang besar, ancaman tersebut salah satunya berasal dari sampah laut, terutama sampah plastik yang tenggelam dan menempel pada karang.…”
Section: Ar Tic Le Infounclassified
“…Coral reef ecosystems are dynamic tropical marine ecosystems with a high level of biodiversity, so it is interesting to study. The coral reefs are coastal protectors from the physical disturbance of seawater and ecologically are habitats, places to find food, and spawn for marine life [10], [20]. [30] also explained that coral reef ecosystems are used by marine life as shelters.…”
Section: Introductionmentioning
confidence: 99%